Datus-gost. Sicily emergency database in modern age - Salvatore Spina (Umanistica Digitale, 2022)
Reconsidering “territories government” in the Modern Age is about analyzing a weak and widespread reality of power, especially when historians have to reconstruct the history of massive emergencies (such as eruptions, earthquakes, epidemics) event which led to a heated debate between Government and the social body. Nevertheless, this debate left a mark in the territory, in the urban planning and the whole life dimension. Datus-Gost aims to compile into a database all these marks, to give back to the scientific community a new tool to be used to write the history of pandemic and natural disaster that stroke Sicily.